2011
DOI: 10.1253/circj.cj-10-0831
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Adaptive Servo-Ventilation for Treating Heart Failure Regardless of the Severity of Sleep-Disordered Breathing

Abstract: Background: It is unclear whether adaptive servo-ventilation (ASV) is effective for all patients with heart failure (HF). The aim of the present study was therefore to investigate the effectiveness of ASV for all patients with HF. Methods and Results:Sixty-one patients with HF were recommended for ASV treatment, regardless of sleepdisordered breathing (SDB) severity and type. On the basis of the apnea - hypopnea index (AHI) results, patients were classified into 3 groups: 28 patients with AHI ≥40/h were design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 25 publications
4
23
0
1
Order By: Relevance
“…There are several reports about a reduction in the BNP level after several months of using ASV. 17,25,29, 30 In the present study, only 'single night' use of ASV directly decreased cardiac overload as demonstrated by significant decreases in the ANP and BNP levels in CHF patients with SDB. This effect by ASV seems to be driven by intrathoracic positive pressure.…”
Section: Effects Of O2 and Asv On Cardiac Overload In Hfsupporting
confidence: 46%
“…There are several reports about a reduction in the BNP level after several months of using ASV. 17,25,29, 30 In the present study, only 'single night' use of ASV directly decreased cardiac overload as demonstrated by significant decreases in the ANP and BNP levels in CHF patients with SDB. This effect by ASV seems to be driven by intrathoracic positive pressure.…”
Section: Effects Of O2 and Asv On Cardiac Overload In Hfsupporting
confidence: 46%
“…However, previously, we reported that ASV therapy for patients with mild SDB resulted in almost equal improvements in brain natriuretic peptide (BNP) and left ventricular ejection fraction (LVEF) compared with patients with moderate and severe SDB, thus demonstrating that ASV therapy was effective for all patients with HF. 9 Similarly, other reports suggested that the ASV therapy improved the LVEF, BNP, and the prognosis of patients with HF. 6,10,11 However, previous reports have suggested that there is a negative relationship between the severity of SDB and prognosis.…”
Section: Introductionmentioning
confidence: 83%
“…Previously, we reported that ASV treatment for patients with mild SDB resulted in comparable improvements in BNP and LVEF to those for patients with moderate and severe SDB. 9 Koyama et al have also reported that ASV therapy for patients with HF effectively improved the short-term prognosis (again, assessed by LVEF and BNP), irrespective of the SDB severity. 21 Moreover, previous reports have revealed that ASV therapy improved both BNP and LVEF.…”
Section: Findings and Data Interpretationmentioning
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, neither the rate of complications of CSR before the intervention nor the results of the 1-year follow-up evaluation of the improvement on SDB after treatment was described in the authors' previous report. 9 As Brown's review shows, because most studies to date have lacked titration of undergoing PSG at a sleep laboratory and of follow-up examination to estimate the efficacy of ASV for each individual patient, there is no support for physicians to indiscriminately prescribe ASV for unselected patients to use in their home with the device parameters set to default values. 14 Consequently, because ASV is a much more complicated device to use than CPAP, it requires greater concern with regard to prescription and management.…”
Section: Article P 661mentioning
confidence: 99%